1990
DOI: 10.1172/jci114557
|View full text |Cite
|
Sign up to set email alerts
|

Early expression of high-affinity receptor for immunoglobulin E (Fc epsilon RI) during differentiation of mouse mast cells and human basophils.

Abstract: The early appearance of FcfRI during cell differentiation may be important for these cells to respond to IgE-mediated stimuli before granulation. The physiologic role of FcERI could be to mediate lymphokine production (IL-3, IL-, IL-6, and granulocyte/macrophage colony-stimulating factor) without inducing cellular degranulation. (J. Clin. Invest. 1990.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 28 publications
4
26
0
Order By: Relevance
“…The number of undifferentiated mast cells detected in the bone marrow with mAb-BGD6 in the present study, 200 per 10 6 cells, is in agreement with the number of mast cell precursors estimated from limiting dilution in vitro assays (291 per 10 6 cells, 28 680 per 10 6 cells, 29 and 924 per 10 6 mononuclear cells 30 ) or from in vivo assays (100 per 10 6 cells 31 ). The number of undifferentiated AA4 Ϫ /BGD6 ϩ mast cells isolated from the bone marrow in this study does not include pluripotent hematopoietic stem cells that have the potential to develop into mast cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The number of undifferentiated mast cells detected in the bone marrow with mAb-BGD6 in the present study, 200 per 10 6 cells, is in agreement with the number of mast cell precursors estimated from limiting dilution in vitro assays (291 per 10 6 cells, 28 680 per 10 6 cells, 29 and 924 per 10 6 mononuclear cells 30 ) or from in vivo assays (100 per 10 6 cells 31 ). The number of undifferentiated AA4 Ϫ /BGD6 ϩ mast cells isolated from the bone marrow in this study does not include pluripotent hematopoietic stem cells that have the potential to develop into mast cells.…”
Section: Discussionsupporting
confidence: 90%
“…[32][33][34][35][36][37][38] Although the freshly isolated AA4 Ϫ /BGD6 ϩ mast cells do contain mRNA for the ␣ and ␤ subunits of Fc⑀RI, the receptor is not expressed on the surface of the freshly isolated cells, consistent with earlier reports on Fc⑀RI expression in rodent bone marrowderived mast cell cultures. 23,29,39,40 However, after time in culture the AA4 Ϫ /BGD6 ϩ mast cells do express Fc⑀RI, bind IgE, can be activated through Fc⑀RI, exhibit the mast cell-specific gangliosides on their surface, as well as contain metachromatic granules. Morphologic studies of rat bone marrow-derived mast cells have shown that the gangliosides recognized by mAb-AA4 are present only on the surface of granulated mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…We call these colonies mast cell or basophil colonies because it is difficult to distinguish these two cell types by light microscopic examination of cytocentrifuged preparations. (25). The alcian bluepositive cells from both the FceR+ and Fc6R-populations of normal mice had only 1 or 2 granules per cell and those from anti-IgD-injected mice had 2-10 granules per cell [i.e., far fewer granules than those present in mature mast cells (19)].…”
Section: Methodsmentioning
confidence: 99%
“…To further confirm the basophil/mast cell lineage of the basophilic granular cells in the LRARc~403SN-infected FDCP mix A4 cells, we utilized flow cytometry to examine the expression of cell-surface immunoglobulin E receptor (IgE R), another basophil/mast cell-specific marker (Metzger et al 1986;Thompson et al 1990). A high percentage (38.4%) of cells expressing surface IgE R was noted in LRARc~403SN-infected cells, whereas only 0.4% of LXSN-infected cells were positive for IgE R (Table 1).…”
Section: Expression Of Rara403 In Fdcp MIX A4 Cells Triggers the Devementioning
confidence: 99%